A sociologia de Raul Seixas: a arte como espelho social de sua época - Bianca Marcia Ferreira (2013)
The research developed on this work attempted producing a set of qualitative data to allow outlining the most significative social relations established by Raul Seixas along his life, trying to understand his personal and artistic "destiny". Observations were made from events in which he was celebrated and from interviews with people who have lived with him. Other sources were the vast material available on the internet and other medias, and also his biography, more directly related to his career. This material is presented initially under the title "A Música" (The Music), where we have exposed Raul's musical influences and the oppressive and contrarian context of the times. Following that, titled "Raul", we introduce important references to his personal journey. In conclusion, we present outlines a summary of the "Configuration of Raul".